Phase I trial of stereotactic MR-guided online adaptive radiation therapy (SMART) for the treatment of oligometastatic or unresectable primary malignancies of the abdomen. Issue 3 (March 2018) - Henke, Lauren; Kashani, Rojano; Robinson, Clifford; Curcuru, Austen; DeWees, Todd; Bradley, Jeffrey; Green, Olga; Michalski, Jeff; Mutic, Sasa; Parikh, Parag; Olsen, Jeffrey
Abstract: Purpose/objectives: SBRT is used to treat oligometastatic or unresectable primary abdominal malignancies, although ablative dose delivery is limited by proximity of organs-at-risk (OAR). Stereotactic, magnetic resonance (MR)-guided online-adaptive radiotherapy (SMART) may improve SBRT's therapeutic ratio. This prospective Phase I trial assessed feasibility and potential advantages of SMART to treat abdominal malignancies. Materials/methods: Twenty patients with oligometastatic or unresectable primary liver ( n = 10) and non-liver ( n = 10) abdominal malignancies underwent SMART. Initial plans prescribed 50 Gy/5 fractions (BED 100 Gy) with goal 95% PTV coverage by 95% of prescription, subject to hard OAR constraints. Daily real-time online-adaptive plans were created as needed, based on daily setup MR-image-set tumor/OAR "anatomy-of-the-day" to preserve hard OAR constraints, escalate PTV dose, or both. Treatment times, patient outcomes, and dosimetric comparisons between initial and adaptive plans were prospectively recorded. Results: Online adaptive plans were created at time of treatment for 81/97 fractions, due to initial plan violation of OAR constraints (61/97) or observed opportunity for PTV dose escalation (20/97). Plan adaptation increased PTV coverage in 64/97 fractions. Zero Grade ≥ 3 acute (<6 months) treatment-related toxicities were observed. Discussion: SMART is clinically deliverable and safe, allowing PTV dose escalation and/or simultaneous OAR sparing compared to non-adaptive abdominal SBRT.